Recent Advances in Camel Immunology - Hussen, Jamal; Schuberth, Hans-Joachim (Frontiers in Immunology, 2021)
Camels are domesticated animals that are highly adapted to the extreme desert ecosystem with relatively higher resistance to a wide range of pathogens compared to many other species from the same geographical region. Recently, there has been increased interest in the field of camel immunology. There is now growing knowledge about camel immunoglobulins that contrasts with findings for camel immune cells. This review intends to summarize published findings related to camel cellular immunology with a focus on the phenotype and functionality of camel leukocyte subpopulations. The review also describes the impact of different physiological (age and pregnancy) and pathological (e.g. infection) conditions on camel immune cells. Despite the progress achieved in the field of camel immunology, there are gaps in our complete understanding of the camel immune system. Questions remain regarding innate recognition mechanisms, the functional characterization of antigen-presenting cells, and the characterization of camel NK and cytotoxic T cells.